2002
DOI: 10.1177/089875640201900403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dental Chew on Dental Substrates and Gingivitis in Cats

Abstract: The use of special diets or dietary adjuncts, although not eliminating the need for regular professional therapy, may serve to improve gingival health during the interval between professional oral health assessments and intervention. This study was performed to determine the effect of a dental chew on dental hygiene and gingival health in cats. The accumulation of dental substrates and the development of gingivitis were assessed in cats fed either a dry diet only or a dry diet supplemented with dental chews. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…A similar study reported dental disease in 13.9% of pet cats in the UK 5 . The high prevalence of dental disease in Persians, regardless of the absence of a predisposition in the breed, suggest that veterinarians could reasonably improve their promotion of preventative periodontal care 88,89 . Evidence for Persian (and Exotic) cats having an increased predisposition of certain dental disorders comes from a recent prospective study where 50 cats were anaesthetized for complete dental examinations and identified 88% with periodontal disease, 76% with abnormal numbers of teeth, 72% with dental malocclusions, 64% with malpositioned teeth and 56% with dental crowding 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar study reported dental disease in 13.9% of pet cats in the UK 5 . The high prevalence of dental disease in Persians, regardless of the absence of a predisposition in the breed, suggest that veterinarians could reasonably improve their promotion of preventative periodontal care 88,89 . Evidence for Persian (and Exotic) cats having an increased predisposition of certain dental disorders comes from a recent prospective study where 50 cats were anaesthetized for complete dental examinations and identified 88% with periodontal disease, 76% with abnormal numbers of teeth, 72% with dental malocclusions, 64% with malpositioned teeth and 56% with dental crowding 32 .…”
Section: Discussionmentioning
confidence: 99%
“…17,18,25,104 The owner is given instructions on daily tooth brushing with a soft-bristled toothbrush and pet dentifrice. 36,40,56,115 For a list of approved products, please visit the website of the Veterinary Oral Health Council (http://vohc.org). 36,40,56,115 For a list of approved products, please visit the website of the Veterinary Oral Health Council (http://vohc.org).…”
Section: Home Oral Hygienementioning
confidence: 99%
“…The dental calculus, gingivitis, and periodontitis were scored using the scheme presented in Table 2, as previously published by Ingham et al (2002). Findings were recorded on standardized feline dental charts.…”
Section: Anaesthesia Dental Examination and Treatmentmentioning
confidence: 99%